1998
DOI: 10.1034/j.1600-0501.1998.090208.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized ridge augmentation using a micro titanium mesh: a report on 27 implants followed from 1 to 3 vears after functional loading

Abstract: The present paper describes the clinical and radiographic healing results of 27 implants followed from 1 to 3 years after functional implant loading. Prior to implant placement, alveolar ridges with insufficient bone volume were augmented using autogenous bone grafts and a micro titanium mesh for graft stabilization. After a mean interval of 5.2 months implants were installed. Following an osseointegration period of on average 7.2 months, implants were supplied with suprastructures. The mean loading period for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 0 publications
2
46
1
1
Order By: Relevance
“…The predictability of this augmentation technique was not so high. Previous studies assessed this procedure and reported good results [7][8][9][10][11]. Our result was inconsistent with them.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The predictability of this augmentation technique was not so high. Previous studies assessed this procedure and reported good results [7][8][9][10][11]. Our result was inconsistent with them.…”
Section: Discussioncontrasting
confidence: 82%
“…Several membranes (non-resorbable and resorbable) have been utilized in order to enhance bone graft stabilization and to minimize the risk of collapse and/or soft tissue dehiscence [5,6]. In recent years, the use of micro titanium mesh in combination with bone grafts and bone substitutes has been proposed and tested for guided/protected bone augmentation [7][8][9][10][11][12]. Localized alveolar ridge augmentation using micro titanium mesh is a method to contain and stabilize the graft materials and also to protect regeneration spaces, allowing better bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-rigid membranes are especially useful to treat the vertical component of the ridge deformity (7). The use of membranes made of titanium micromesh has been advocated (37)(38)(39)(40). Aim of the present study was a clinical evaluation of the results obtained in GBR with titanium micromesh and a resorbable membrane in aesthetic areas.…”
Section: Three Case Reportsmentioning
confidence: 99%
“…There are two types of membrane: resorbable and nonresorbable. One of the main problems in using occlusive membranes is their lack of stiffness that can produce a collapse of the barrier towards the bone defect, reducing in such a way the space needed for the bone regeneration (38)(39)(40)44). This problem can be, in part, overcome with the use of grafts beneath the membrane, but the influence of the overlying soft tissues in collapsing the membrane could still be present.…”
mentioning
confidence: 99%
“…그러나 e-PTFE 차폐막은 견고성이 떨어져 치유기 간동안 차폐막의 함몰이 관찰되었고 [17][18][19] , [23][24][25][26][27][28][29][30] . 티타늄을 사용한 차폐막 중 직조 형 티타늄막이 임상적으로 많이 사용되고 있으며, 이는 적당한 견고성을 가지고 있고, 잔존 치조제에 적합도도 우수하나 25) , 천공이 없는 폐쇄성 차폐막은 적당한 견고성을 가지는 두께 때문에 치조제 적합성 이 떨어진다 31) .…”
unclassified